THE PRINCIPLE OF THE BEST INTERESTS OF THE CHILD - Ioana PĂDURARIU (Challenges of the Knowledge Society, 2019)
Since 1919, the recognition of children's rights has begun to find an international echo, when the League of Nations ”came to life”, the name of which links to the Geneva Declaration of 1924. Adopted in 1989, by the Convention on the Rights of the Child, the principle of the best interests of the child is still an imprecise, subjective notion if we consider its application, but so necessary, even in the absence of precise regulatory criteria.